The damselfly genus Megaloprepus (Odonata: Pseudostigmatidae): Revalidation and delimitation of species-level taxa including the description of one new species - Feindt, Wiebke; Hadrys, Heike (Zootaxa, 2022)
As the longest-winged odonate species of the extant world, Megaloprepus caerulatus (Drury, 1782) has received attention by many entomologists. While the behavior and ecology of this species has been subject of intense studies, biogeography and species status throughout its distributional range in old-growth Neotropical forests are less well known. For tropical forests, this information is a sine qua non when estimating the impact of degradation and climate change. Recent population genetic analyses, quantitative morphometric, and traditional taxonomic studies rediscovered a complex composed of cryptic species within the genus Megaloprepus Rambur, 1842—up until now still regarded as a monotypic genus. Here we introduce one new species Megaloprepus diaboli sp. nov. from the southern Pacific coast of Costa Rica and from the central Caribbean coast of Honduras and Guatemala. The holotype is from the Corcovado National Park, Costa Rica (N 8°28’55.62” W 83°35’13.92”), and was deposited at the National Museum of Costa Rica. Aside from M. caerulatus, two formerly described and later refused species within the genus were reevaluated and consequently raised to species status: Megaloprepus latipennis Selys, 1860 is found in the northeastern regions of Mesoamerica and Megaloprepus brevistigma Selys, 1860 in South America east of the Andes. Morphological descriptions of selected specimens (holotype of M. diaboli, lectotype of M. latipennis, and the mature males of M. brevistigma and M. caerulatus) are provided. Diagnostic features of the four species are illustrated, discussed, and summarized in a key to adult males.